1994
DOI: 10.1017/s0022215100126076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hearing loss in electrocochleographic investigation of endolymphatic hydrops using tone-pip and click stimuli

Abstract: Extratympanic electrocochleography (ECochG) was performed on 37 patients referred to the Evoked Potential Clinic with suspected Ménière's disease. The patients were classified according to their hearing impairment and audiometric configuration. Click and tone-pip stimuli with tone frequencies of 1 and 4 kHz were presented at a rate of 10 per second. Amplitude, latency and general waveform characteristics of the summation potential (SP) and action potential (AP) were analysed for each averaged response with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
4
0
4
Order By: Relevance
“…Unfortunately, a number of variables can significantly affect the results and diagnostic value of the SP, as well as the SP/AP ratio measures; in particular, hearing loss (8,17).…”
Section: Hypothesis: Endolymphatic Hydrops In Patients Diagnosed Withmentioning
confidence: 99%
“…Unfortunately, a number of variables can significantly affect the results and diagnostic value of the SP, as well as the SP/AP ratio measures; in particular, hearing loss (8,17).…”
Section: Hypothesis: Endolymphatic Hydrops In Patients Diagnosed Withmentioning
confidence: 99%
“…Traditionally, it has been more com mon to use toneburst stimuli for TT record ings only. Recently, however, tonebursts have [17] 110 dBSPL TM Mean -0.27 SD 0.17 Margolis et al [9] 110 dB SPL TM Mean -0.66 -0.96 SD 0.52 0.77 been applied in several TM studies [9,11,17,20,21 ]. One advantage of using tonebursts in addition to clicks is that a higher degree of response frequency specificity can be achieved.…”
Section: Click Versus Tonebursl Stimulimentioning
confidence: 99%
“…The decision to use a certain criteri on value is further complicated by the fact that the rate of detection of MD based on an enhanced SP depends on the degree of hearing loss. Koyuncu et al [11], for example, found a greater incidence of abnormal SP amplitudes for patients with an average hearing loss in the range of 40-60 dB HL than for those with a Audiol Ncuroatol 1997;2:241-256hearing loss greater than 65 dB HL or between 0 and 39 dB HL. Gibson [33] suggested lower ing the criterion value for subjects with marked hearing loss to reduce the incidence of false-positive and false-negative results.…”
Section: Identification and Monitoring O F Meniere's Diseasementioning
confidence: 99%
“…Bei deren Mitbeteiligung verlän-gert sich die Laufzeit der Wanderwelle, bis sie intakte Haarzellen antrifft, und damit auch die CAP-Latenz. So ist die CAP-Latenz bei Innenohrschwerhörigkeit mit zunehmender Hörminderung verlängert [27], ebenso beim M. Menire bei pantonalem Hörverlust und geringer Fluktuation [14]. Ein weiter CAP-Komplex weist auf eine Desynchronisation der neuralen Einzelfaserantworten hin und wird häufig beim Akustikusneurinom [28], aber auch beim fortgeschrittenen M. Menire beobachtet [29].…”
Section: Ergebnisseunclassified
“…Ein weiter CAP-Komplex weist auf eine Desynchronisation der neuralen Einzelfaserantworten hin und wird häufig beim Akustikusneurinom [28], aber auch beim fortgeschrittenen M. Menire beobachtet [29]. Die CAP-Weite korreliert bei Menire-Patienten signifikant mit dem Ausmaû des Hörverlustes [27]. Heruntergeladen von: University of Florida.…”
Section: Ergebnisseunclassified